Swimming Attenuates Muscle Wasting and Mediates Multiple Signaling Pathways and Metabolites in CT-26 Bearing Mice - Li, Jiapeng; Xie, Qiurong; Liu, Liya; Cheng, Ying; Han, Yuying; Chen, Xiaoping; Lin, Jia; Li, Zuanfang; Liu, Huixin; Zhang, Xiuli; Chen, Haichun; Peng, Jun; et al. (Frontiers in Molecular Biosciences, 2022)
Objectives: To investigate the effects of swimming on cancer induced muscle wasting and explore its underlying mechanism in CT-26 bearing mice. Methods: BALB/c mice (n=16) injected with CT-26 cells were divided into two groups, including Tumor group (n=8) and Swimming group (n=8). Another 8 un-injected mice were set as Control group. Mice in Swimming group were subjected to physical training for swimming twice per day for 30 min intervals and 6 days per week for a total of 4 weeks. The tumor volume was monitored every 3 days and tumor weight was measured at the end of experiment. The changes of muscle function, pathological and cell apoptosis of quadriceps muscles were further assessed, and its underlying mechanisms were further explored using multiple biological technologies. Results: Swimming obviously alleviated tumor volume and weight in CT-26 bearing mice. Moreover, swimming attenuated the decrease of muscle tension, autonomic activities, and increase of muscle atrophy, pathological ultrastructure, as well as cell apoptosis of quadriceps muscles in CT-26 bearing mice. Furthermore, swimming significantly down-regulated the protein expression of NF-κB, p-NF-κB, TNF-α, IL-1β, IL-6 and Bax, while up-regulated the expression of Bcl-2. Further differential expressed metabolites (DEMs) analysis identified a total of 76 (in anion mode) and 330 (in cationic mode) DEMs in quadriceps muscles of CT-26 bearing mice after swimming, including taurochenodeoxycholic acid, taurocholic acid, ascorbic acid and eicosapentaenoic acid. Conclusion: Swimming attenuates tumor growth and muscle wasting, and by suppressing the activation of NF-κB signaling pathway mediated inflammation, reducing the level of Bax medicated cell apoptosis, as well as modulating multiple metabolites might be the importantly underlying mechanisms.